Exploring stakeholders and their requirements in the process of home hemodialysis: A literature review. Issue 1 (9th September 2021) - Khan, Ilyas; Pintelon, Liliane; Martin, Harry; Khan, Rahmat Ali
Abstract: Providing home hemodialysis (HHD) therapy is a complex process that not only requires the use of a complex technology but also involves a diverse group of stakeholders, and each stakeholder has their requirements and may not share a common interest. Bringing them together will require the alignment of their interests. A process management perspective can help to accomplish the alignment of their interests. To align their interests, it is crucial to identify interest groups and understand their interests. The main objective of this paper is to identify the stakeholders and represents their interests as a list of requirements in the HHD process. An extensive literature review has been carried out and PubMed was used for literature extraction. In total, 1848 articles were retrieved of which 80 have fulfilled the inclusion criteria. A large array of actors is identified and their interests/requirements at different stages of the HHD process are represented in the form of a list. They have both common and conflicting requirements in the HHD process. If these requirements are aligned and balanced, a stakeholder's driven treatment process will be developed and a real improvement will be achieved in the treatment process.